Cardiovascular Adaptation And Functional Responses To Physical Stress In Children And Adolescents With Undifferentiated Connective Tissue Dysplasia (Texas Journal of Medical Science, 2025)
Undifferentiated connective tissue dysplasia (UCTD) is a genetically determined condition characterized by systemic manifestations affecting multiple organs, including the cardiovascular system. Children and adolescents with UCTD demonstrate impaired structural, functional, and autonomic regulation of cardiac activity, which reduces their tolerance to physical stress.